NEW INTERPRETATION OF NAVOI IMAGE (On the example of Omon Mukhtor's "Navoi and Artist Abulkhair" novel) (Scientific journal of the Fergana State University, 2023)
The article explores the skill of creating Oman Mukhtar's image, in particular the interpretation of Navoi's image. The peculiarities of the exploration of the Navoi embodiment from the perspective of the artist and writer are examined